(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Plasma osmolality (pOsmol) and neurohumoral signals play important roles in the pathophysiology of cardiovascular diseases. Our study investigated the effect of high environmental temperature (HET) on neurohumoral responses and pOsmol in rats fed a high salt diet (HSD), with and without angiotensin II receptor blockade (ARB), using telmisartan. Fifty-six male 8-week old Sprague-Dawley rats (95-110g) were randomly assigned into seven groups of 8 rats. These included control rats (I) fed with 0.3% NaCl diet (normal diet, ND); salt-loaded rats (II) fed with 8% NaCl (high salt) diet; ND rats (III) exposed to HET (38.5±0.5oC ) 4 hours daily per week; rats (IV) fed with 8% NaCl diet and exposed to HET daily. Others included rats (V) fed with 8% NaCl diet and treated with telmisartan (30mg/kg); ND rats (VI) exposed to HET and treated with telmisartan; rats (VI) fed with 8% NaCl diet, exposed to HET and treated with telmisartan. Plasma angiotensin II, aldosterone, vasopressin and norepinephrine (NE) concentrations were determined by ELISA technique; pOsmol from plasma K+, Na+ and Urea. HSD combined with HET in rats synergistically increased pOsmol (P<0.001) with an associated non-synergistic rise in fluid intake (P<0.001), fluid balance (P<0.001), plasma angiotensin II (P<0.01) and aldosterone (P<0.05), NE (P<0.001) and vasopressin (P<0.05) concentrations compared to control. Telmisartan did not alter pOsmol in all the treated-rats, but normalized fluid intake levels and plasma vasopressin in the rats exposed to either HSD or HEt alone. Prolonged exposure of rats to hot environment exacerbated the effect of excess dietary salt on pOsmol, with no effect on angiotensin II-mediated neurohumoral responses